2014
DOI: 10.1538/expanim.63.141
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Weak Acid Hypochlorous Solution on Selected Viruses and Bacteria of Laboratory Rodents

Abstract: Weak acid hypochlorous solution (WAHS) is known to have efficacy for inactivating pathogens and to be relatively safe with respect to the live body. Based on these advantages, many animal facilities have recently been introducing WAHS for daily cleaning of animal houses. In this study, we determined the effect of WAHS in inactivating specific pathogens of laboratory rodents and pathogens of opportunistic infection. WAHS with an actual chloride concentration of 60 ppm and a pH value of 6.0 was generated using p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…Other germicidal agents, such as hypochlorous acid fogs, used at a concentration of 600 ppm for 10 minutes following removal of all organic matter have demonstrated some efficacy in clinical settings 78 …”
Section: Engineering Controls: Methods To Mitigate Microbial Payload In Aerosolsmentioning
confidence: 99%
“…Other germicidal agents, such as hypochlorous acid fogs, used at a concentration of 600 ppm for 10 minutes following removal of all organic matter have demonstrated some efficacy in clinical settings 78 …”
Section: Engineering Controls: Methods To Mitigate Microbial Payload In Aerosolsmentioning
confidence: 99%
“…In addition, the increase in reduction of the quantified HA titer in the inoculated embryonated eggs with more elongation of the contact time between the H9N2 virus and the EOB provided evidence on the effectiveness of this blend in reducing the ability of the surviving H9N2 particles to propagate. It is worth noting that other works pointed at sanitizers that injure viruses, thus lowering their ability to multiply in the host cells [49][50][51]. Moreover, the 100% survival of the embryos inoculated by the transport medium, containing only the collected vapor of the EOB, is indicative of the vapor's safety, a data that is in agreement with another work that reported the safety of direct inoculation in chicken embryos of high concentrations of the liquid phase of an equivalent ratio of Eucalyptus and peppermint (1/1 V/V) [52].…”
Section: Anti-pulverized H9n2 Virus By Vapors Of the Essential Oil Blmentioning
confidence: 99%
“…Environmental cleanup in such facilities is carried out using a chlorhexidine or phenolic disinfectant, and/or by supplying antibiotics, or tap water acidified with hydrochloric acid at pH 2.5 to 3.0. Recently, effectiveness of the weak acid hypochlorous solution in vitro on various microorganisms including P. aeruginosa was reported [ 5 , 7 ]. On the other hand, the solution used as disinfectant for drinking water was ineffective as the effectiveness of HClO in the weak acid hypochlorous solution is possibly decreased by contact with organic materials in the stomach and intestine, and the effect of the weak acid hypochlorous solution on murine Norovirus was limited to the small intestine [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…HClO has been reported to be effective against various microorganisms [ 5 ], while on the other hand, the efficacy of HClO in solution is decreased possibly due to contact with organic material in the stomach and intestine, and therefore when added to drinking water for animals, it has not been proven effective in eliminating pathogens [ 9 ]. Taharaguchi et al have suggested the use of weak acid hypochlorous solution for routine cleaning in animal facilities, but they also point out that the effect could be reduced due to the presence organic material [ 7 ]. The effect of weak acid hypochlorous solution on murine Norovirus in the mouse cecum has been reported to be limited [ 8 ].…”
Section: Introductionmentioning
confidence: 99%